Disaster perception and psychosocial responses in the community of Tartagal, Argentina: a qualitative study of the 2009 landslide - Abeldaño, Roberto Ariel; Lucchese, Marcela Susana; Fernández, Alicia Ruth (Revista Chilena de Salud Pública, 2015)
On February 9, 2009 in Tartagal, Argentina, an avalanche of water, mud and trees burst into the city causing three deaths, ten missing people and over a thousand evacuees. The aim of the present work was to analyze the perceptions and experiences of affected individuals with regard to the landslide, and psychosocial responses to the disaster. A qualitative approach was used to explore the perceptions and experiences of 23 subjects interviewed in 2013. The information was analyzed using the Grounded Theory. The responses elicit theoretical categories related to the perception of the disaster and its effects, and the psychosocial responses displayed by the disaster situation become apparent. The avalanche was experienced as a disaster causing deaths, destruction and losses suffered by individuals and families. Among the effects of the disaster, a number of psychosocial responses were observed, including sensations of interrupted communication, as well has housing and property losses. We conclude that psychosocial responses to disaster depend on a combination of risk factors and resilience.